ChemInform Abstract: A Facile Clean Synthesis of Pyrido[2, 3‐d]pyrimidine and Their Derivatives in Ionic Liquids. Issue 15 (April 2015) - Yadav, Ashok K.; Gupta, Manisha
Abstract: Chalcones react with malononitrile in ionic liquid affording 2‐amino‐3‐cyano‐4, 6‐disubstituted pyridines (III) as precursor for efficient syntheses of a new type of pyrido[2, 3‐d]pyrimidine derivatives.